Interfacial Engineering of Perovskite Solar Cells by Employing a Hydrophobic Copper Phthalocyanine Derivative as Hole‐Transporting Material with Improved Performance and Stability. Issue 8 (16th March 2017) - Jiang, Xiaoqing; Yu, Ze; Lai, Jianbo; Zhang, Yuchen; Hu, Maowei; Lei, Ning; Wang, Dongping; Yang, Xichuan; Sun, Licheng
Abstract: In high‐performance perovskite solar cells (PSCs), hole‐transporting materials (HTMs) play an important role in extracting and transporting the photo‐generated holes from the perovskite absorber to the cathode, thus reducing unwanted recombination losses and enhancing the photovoltaic performance. Herein, solution‐processable tetra‐4‐(bis(4‐ tert ‐butylphenyl)amino)phenoxy‐substituted copper phthalocyanine (CuPc‐OTPA t Bu) was synthesized and explored as a HTM in PSCs. The optical, electrochemical, and thermal properties were fully characterized for this organic metal complex. The photovoltaic performance of PSCs employing this CuPc derivative as a HTM was further investigated, in combination with a mixed‐ion perovskite as a light absorber and a low‐cost vacuum‐free carbon as cathode. The optimized devices [doped with 6 % ( w / w ) tetrafluoro‐tetracyano‐quinodimethane (F4TCNQ)] showed a decent power conversion efficiency of 15.0 %, with an open‐circuit voltage of 1.01 V, a short‐circuit current density of 21.9 mA cm −2, and a fill factor of 0.68. Notably, the PSC devices studied also exhibited excellent long‐term durability under ambient condition for 720 h, mainly owing to the introduction of the hydrophobic HTM interlayer, which prevents moisture penetration into the perovskite film. The present work emphasizes that solution‐processable CuPc holds a great promise as a class of alternative HTMs that can be further explored for efficient and stable PSCs in the future. Abstract : Lighten up : Solution‐processable tetra‐4‐(bis(4‐ tert ‐butylphenyl)amino)phenoxy‐substituted copper phthalocyanine (CuPc‐OTPA t Bu) is synthesized and explored as a hole‐transporting material (HTM) in perovskite solar cells, showing a decent efficiency of 15.0 % together with excellent long‐term stability.